Perbandingan Angka Kejadian Karies Gigi Antara Asi dan Susu Formula pada Anak Usia Dua Tahun - Ni Luh Krisna Agustini; Wahyuni Dyah Parmasari (Indonesian Journal of Dentistry, 2021)
Background: Breast Milk (ASI) be source of best nutrition for baby and child of especially in 6th month. ASI very useful for development of brain and body endurance, and can tighten the relation of affection between mothers and baby. One important things at composition ASI that is doesn't contain sucrose. Sucrose defined since beginning of at baby will influence preferensi / selera food, what can cause health trouble risk. Method: This research type is analytic of observasional with design cross sectional. Technics of sampling applies is probability sampling a number of 50 responders. Result: In this research shows there are comparison of dental caries between ASI and formula milk at child of age 6 month of until 2 year with valuable F test 6,422 with probability ( p) = 0,003<0,05. Conclusion: There is positive comparison of dental caries between ASI and formula milk at responder where more baby drinking formula milk, hence there will be improvement of case number of dental caries at age baby 6th month until 2 year in Kecamatan Kuta Kabupaten Badung Provinsi Bali.